"Cov(aX+bY,cX+dY)=Cov(aX,cX+dY)+Cov(bY,cX +dY)="
"Cov(aX,cX)+Cov(aX,dY)+Cov(bY,cX)+Cov(bY,dY)="
"ac\\ Cov(X,X)+ad \\ Cov(X,Y)+bc\\ Cov(Y,X)+bd \\ Cov (Y,Y)="
"ac \\ Var(X)+ad\\ Cov(X,Y)+bc\\ Cov(X,Y)+bd \\ Var(Y)="
"=ac \\ Var(X)+bd\\ Var(Y)+(ad+bc)Cov(X,Y)"
So, "Cov(aX+bY,cX +dY)=ac \\ Var(X)+bd \\ Var(Y)+(ad+bc)Cov(X,Y)"
The following properties were used:
"Cov(X,Y)=Cov(Y,X)"
"Cov(aX,Y)=a\\ Cov(X,Y)"
"Cov(X+Y,W)=Cov(X,W)+Cov(Y,W)"
"Cov (X,X)=Var(X)"
Answer: this statement is true.
Comments
Leave a comment